2016
DOI: 10.1073/pnas.1517994113
|View full text |Cite
|
Sign up to set email alerts
|

Targeting theGdnfGene in peritubular myoid cells disrupts undifferentiated spermatogonial cell development

Abstract: Spermatogonial stem cells (SSCs) are a subpopulation of undifferentiated spermatogonia located in a niche at the base of the seminiferous epithelium delimited by Sertoli cells and peritubular myoid (PM) cells. SSCs self-renew or differentiate into spermatogonia that proliferate to give rise to spermatocytes and maintain spermatogenesis. Glial cell line-derived neurotrophic factor (GDNF) is essential for this process. Sertoli cells produce GDNF and other growth factors and are commonly thought to be responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
131
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(135 citation statements)
references
References 72 publications
2
131
1
1
Order By: Relevance
“…The GDNF, secreted by Sertoli cells and peritubular myoid cells, is the major paracrine factor specifically responsible for the maintenance and self-renewal of SSCs in vivo (29,30). Other signaling pathways like insulinlike growth factor-1 receptor (IGF-1R) (31) mediated and fibroblast growth factor 2 (FGF2) (32) mediated pathways also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…The GDNF, secreted by Sertoli cells and peritubular myoid cells, is the major paracrine factor specifically responsible for the maintenance and self-renewal of SSCs in vivo (29,30). Other signaling pathways like insulinlike growth factor-1 receptor (IGF-1R) (31) mediated and fibroblast growth factor 2 (FGF2) (32) mediated pathways also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that PMCs also secrete a number of biomolecules, such as peritubular factors that modulate Sertoli cell function (PModS) [35], fibroblast growth factor 2 (FGF2) [36], colony stimulating factor 1 (CSF1) [37], and Insulin-like growth factor 1 (IGF1) [36], which thus modulate testis microenvironment in adult animals. PMC was also found to involve in testicular growth in postnatal rat testis [38] and spermatogenesis through androgen signaling [39, 40], Lgr4-Wnt/β-catenin signaling [41] and glial cell line-derived neurotrophic factor (GDNF) [40, 42] in adult mouse testis. However, little is known about the function of PMC during fetal testis development.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the Sertoli lines established either by transgenic animals or gene infection had been widely applied for spermatogenesis mediation or investigation of Sertoli cells themselves272829, the application of Sertoli cells for SSC growth has not been validated. Recently testosterone-regulated GDNF secretion by peritubular myoid cells has also been observed, which ensured the optimal GDNF level for repopulating the undifferentiated spermatogonia including SSCs30. However, testis somatic cell feeders were likely to inhibit SSCs survival and replication in vitro 9, and it is unknown whether the overexpression of GDNF and/or other growth factors in STO or MEF could support SSC survival or the long-term proliferation of a SSC line.…”
Section: Discussionmentioning
confidence: 99%